Produção, propriedades e aplicação de celulases na hidrólise de resíduos agroindustriais Production, properties and application of cellulases in the hydrolysis of agroindustrial residues - Aline Machado de Castro; Nei Pereira Jr (Química Nova, 2010)
Cellulases have been intensively studied in the past few years, due to the interests in biofuels production from lignocellulosic materials, since they permit maintaining mild conditions during the conversion process. These enzymes can be produced by a broad variety of naturally occurring microorganisms, such as from genera Aspergillus, Trichoderma, Penicillium and Humicola. Targeting the increasing of expression levels, molecular biology tools have been used for heterologous genes insertion in host cells, e. g., Pichia pastoris and Escherichia coli. Enzymes from fungal cellulolytic complex usually act best at pH between 4 and 5 under temperatures from 40 to 60 °C and can be used for either sequential (SHF) or simultaneous (SSF) hydrolysis together alcoholic fermentation. In this review, the main raw materials for production of cellulases are identified, as well as the state of art of enzymes' properties, production and main applications.